2004
DOI: 10.1016/j.ab.2004.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive methods to determine the critical micelle concentration of some bile acid salts

Abstract: In this work the critical micelle concentrations (cmc) of four bile salts, sodium cholate, sodium glycocholate, sodium deoxycholate, and sodium glycodeoxycholate, are determined and presented. Three independent noninvasive methodologies (potentiometry, derivative spectrophotometry, and light scattering) were used for cmc determination, at 25 degrees C with ionic strength adjusted to 0.10 M with NaCl. Spectrophotometric and potentiometric studies of some bile salts were also executed at various ionic strength v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
122
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(141 citation statements)
references
References 44 publications
19
122
0
Order By: Relevance
“…It has been reported that the CMC of NaDC and NaGC at 25°C with ionic strength adjusted to 0.10 M with NaCl was 2.35 and 11.60 mM, respectively (Reis et al, 2004). Therefore, the used bile salt concentrations were much higher than CMC, regardless of ratio, considering that dilution is minimal in the stomach.…”
Section: Resultsmentioning
confidence: 96%
“…It has been reported that the CMC of NaDC and NaGC at 25°C with ionic strength adjusted to 0.10 M with NaCl was 2.35 and 11.60 mM, respectively (Reis et al, 2004). Therefore, the used bile salt concentrations were much higher than CMC, regardless of ratio, considering that dilution is minimal in the stomach.…”
Section: Resultsmentioning
confidence: 96%
“…The mixed micellar system used in this method consisted of a mixture of six bile salts (NaDC, NaC, NaTDC, NaTC, NaGC and NaGDC) which included dihydroxy, trihydroxy, conjugated and unconjugated bile salts with lecithin phospholipid in 0.15 M NaCl with the pH controlled by HEPES buffer at 6.5. The CMC of the mixed micellar system was deemed to be 0.0046 M based on the average value of the CMCs of the bile salts included in the mixture in 0.15 M NaCl [NaTC CMC = 0.004 M (Natalini et al, 2014), NaDC CMC = 0.0024 M (Natalini et al, 2014), NaTDC CMC = 0.0024 M (Natalini et al, 2014), NaC CMC = 0.0075 M (Reis et al, 2004), NaGC CMC = 0.009 M (Natalini et al, 2014) and NaGDC CMC = 0.0022 M (Natalini et al, 2014)]. The bile salt–lecithin mixed micellar solution was used over a concentration range 0.005–0.017 M. The mixed micellar system was prepared in molar ratios similar to that present physiologically (Wiedmann et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Spectrophotometry in the absence of exogenous probe molecules has proved to be effective in revealing the formation of low aggregation number BA assemblies [37,38]. The CMC can be identified by monitoring the profile of variation of some intrinsic property of the system (such as Abs max around 195-200 nm of the main characteristic UV band) with the surfactant concentration [37].…”
Section: Chromatographic Cmc Estimationmentioning
confidence: 99%
“…The CMC can be identified by monitoring the profile of variation of some intrinsic property of the system (such as Abs max around 195-200 nm of the main characteristic UV band) with the surfactant concentration [37].…”
Section: Chromatographic Cmc Estimationmentioning
confidence: 99%